Pengaruh Struktur Kepemilikan Terhadap Financial Distress serta Implikasinya kepada Manajemen Laba - Risma Rosifah; Rudi Zulfikar; Agus Sholikhan Yulianto (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
Analyzing the impact of ownership structure, namely management ownership, institutional ownership, and ownership concentration on financial hardship is the goal of this study, then consider how financial crisis affects the administration of earnings. A transportation firm listed on the Indonesia stock market from 2016 to 2021 served as the study's sample. The transportation company's annual report was the source of the data, which was gathered through documentation and observation. SPSS version 26 was used to analyse the data using a multiple linear regression strategy. The findings revealed managerial ownership and institutional ownership had positive and negative impact on financial distress. Ownership concentration no impact on financial distress. Financial distress had positive impact on earnings management.